Enantioselective OTUD7B fragment discovery through chemoproteomics screening and high-throughput optimisation - Aini Vuorinen; Cassandra R. Kennedy; Katherine A. McPhie; William McCarthy; Jonathan Pettinger; J. Mark Skehel; David House; Jacob T. Bush; Katrin Rittinger (Communications Chemistry)
Abstract Deubiquitinating enzymes (DUBs) are key regulators of cellular homoeostasis, and their dysregulation is associated with several human diseases. The ovarian tumour protease (OTU) family of DUBs are biochemically well-characterised and of therapeutic interest, yet only a few tool compounds exist to study their cellular function and therapeutic potential. Here we present a chemoproteomics fragment screening platform for identifying novel DUB-specific hit matter, that combines activity-based protein profiling with high-throughput chemistry direct-to-biology optimisation to enable rapid elaboration of initial fragment hits against OTU DUBs. Applying these approaches, we identify an enantioselective covalent fragment for OTUD7B, and validate it using chemoproteomics and biochemical DUB activity assays.